Creating Love Letters to Nature: A Case Study of Children’s Multimodal Literacy Practices - Du, Xiaoxiao; Kuan, Kaiqi (Journal of the Canadian Association for Curriculum Studies, 2020)
Canada welcomes large numbers of immigrants each year, including children. It is certainly important to understand immigrant children’s educational experience beyond standardized tests in reading and math. This paper draws on a sociocultural approach by situating language and literacy learning in social and cultural contexts and by emphasizing the active role of learners in different contexts. Specifically, the multiliteracies framework (The New London Group, 1996) is used to understand how culturally and linguistically diverse (CLD) children choose to use different literacies and modes to make sense of their surroundings and to create artistic texts to express their understandings of nature, such as water and forests. A qualitative case study was conducted to understand five CLD children’s meaning-making process in a community setting. Data was collected through observations, informal conversations, semi-structured interviews and artifacts. The initial findings of the study indicate that CLD children are active and creative meaning-makers who select different linguistic, cultural and artistic resources as well as various modalities to effectively express their ideas and perspectives according to audience, purpose and context. The presentation discusses two nature projects and shares the artwork of the participating children to highlight a range of multilingual, multicultural and multimodal literacy practices.